The Use of STAD to Improve Students’ Writing Skill - Suryani, Suryani; Azlim, Azlim (Journal of ELT Research, 2018)
This study aims to know whether Student Team Achievement Division (STAD) can improve students’ ability in writing descriptive text or not. To answer this research questions, the researchers applied experimental study. Two classes of the second-grade students in MTs (Islamic Junior Secondary School) Babun Najah were chosen as the sample of this study. In order to get the data, the test was used as the main research instrument. The researcher applied teaching writing descriptive text by using STAD in the experimental class. Based on the result, it was found that the t-test score of post-test in experimental and control groups is higher than the t-table score (4.21>1.69). This means that the alternate hypothesis was accepted or the implementation of STAD improves the students’ ability in writing descriptive text. The findings also revealed that the writing component that had improved by using STAD is the content component. The students show more knowledgeable in their writing. In addition, through STAD the students had the opportunity to work together in a group to share and learn in order to produce good writing.                                                                                                                        Keywords: STAD, writing ability, descriptive text